New records of Paravandellia oxyptera Miranda Ribeiro 1912 (Vandelliinae, Siluriformes) in Argentina - Contrera, Guadalupe (2025)
Paravandellia oxyptera Miranda-Ribeiro, 1912, a species of miniature catfish belonging to the subfamily Vandelliinae, is recorded for the first time from the Colastiné River (31º37`9.87” S, 60º34`43.37” W at 14 m elevation), near Laguna Setubal, in the locality of San José del Rincón, Santa Fe Province, Argentina. The specimens were collected using hand nets and seine nets, and represent the first known records of the species for this province. Osteological data from the examined material are also provided.